1997
DOI: 10.1097/00007890-199706270-00012
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial Comparing Interleukin-2 Receptor Antibody Versus Antithymocyte Globulin as Part of a Quadruple Immunosuppressive Induction Therapy Following Orthotopic Liver Transplantation

Abstract: Our results indicate that treatment with anti-interleukin-2 receptor antibody as part of quadruple induction therapy after orthotopic liver transplantation is safe and effective and shows fewer steroid-sensitive rejection episodes as well as fewer side effects when compared with quadruple induction therapy including ATG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…The expression of CD25 on T cells in the patients treated with ATG was found to be significantly lower than in non-ATG-treated patients at least 2 years postoperatively [6]. The IL-2/IL-2 receptor (IL-2R)-system plays an essential role in the antigenspecific clonal expansion of resting T cells within ongoing graft rejection [32, 351. Immunosuppressive agents directed against the IL-2R are of highly immunosuppressive potency [22,24,25,411. In contrast to other studies, a reduced incidence or severity of acute hepatic allograft rejection could not be found, despite the reduced CD25 expression, as well as the reduced percentage of T cells, especially of CD4+ T cells [13, 30, 33, 371. In addition, the expression of IL-2R (CD25) is necessary for the increased expression of the transferrin receptor (CD71), which is essential for the initiation of proliferation in nai've T cells.…”
Section: ~~~mentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of CD25 on T cells in the patients treated with ATG was found to be significantly lower than in non-ATG-treated patients at least 2 years postoperatively [6]. The IL-2/IL-2 receptor (IL-2R)-system plays an essential role in the antigenspecific clonal expansion of resting T cells within ongoing graft rejection [32, 351. Immunosuppressive agents directed against the IL-2R are of highly immunosuppressive potency [22,24,25,411. In contrast to other studies, a reduced incidence or severity of acute hepatic allograft rejection could not be found, despite the reduced CD25 expression, as well as the reduced percentage of T cells, especially of CD4+ T cells [13, 30, 33, 371. In addition, the expression of IL-2R (CD25) is necessary for the increased expression of the transferrin receptor (CD71), which is essential for the initiation of proliferation in nai've T cells.…”
Section: ~~~mentioning
confidence: 99%
“…In liver transplantation, several authors analyzed the effect of ATG on the incidence of acute rejection episodes, severe infectious complications, patient and graft survival, and secondary malignancies after transplantation. These studies showed the efficacy of polyclonal antibody induction therapy on both short-time and long-time clinical outcome of hepatic allografts [16,23,29,30,331. On the other hand, studies on cellular immune response focused on the early postoperative phase [23].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[9][10][11][12] These triple or quadruple immunosuppressive protocols with ATG were proven to have low incidences of rejection with equivalent outcome. We recently reported the first pilot trial using RATG with tacrolimus and MMF and the total absence of steroids in OLT.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] RATG in conjunction with steroids has been shown to effectively reduce the incidence of rejection in OLT without an increased incidence of infectious complications or malignancy. 9,10,12 We previously reported a pilot trial showing the safety and efficacy of a 2-dose regimen of RATG without steroids in OLT. 13 The purpose of this ongoing prospective randomized trial is to eliminate steroid use in OLT through induction with RATG in an effort to determine the need for steroids in OLT and prevent the adverse effects of steroids in liver transplant recipients.…”
mentioning
confidence: 99%